Effects of Short-Term Exposure to Dispersed Oil in Arctic Invertebrates - Mageau, C.; Engelhardt, F.R.; Gilfillan, E.S.; Boehm, P.D. (ARCTIC, 1987)
A series of experimental studies was carried out as part of the Baffin Island Oil Spill (BIOS) Project to define the behavioural, physiological and biochemical reactions of three arctic marine benthic invertebrate species exposed to chemically dispersed crude oil. Behavioural responses and patterns of hydrocarbon accumulation and release observed in the bivalves and the urchin during the 1981 field spill were similar to those observed during the laboratory simulations. Ostial closure, loss of responsiveness to mechanical stimuli and narcosis were characteristic of the bivalves. Exposed urchins displayed a functional loss of tube foot and spine behaviour. Detailed hydrocarbon analysis indicated different uptake dynamics among the species. The effects of dispersed oil were immediate and short lived and resulted in temporary accumulation of hydrocarbons. Depuration of these stored hydrocarbons occurred during the experimental recovery period. In vivo biodegradation of hydrocarbons was indicated in the bivalves. Physiological parameters measured in bivalves exposed to oil included elements of scope for growth, activity of aspartate aminotransferase and glucose-6-phosphate dehydrogenase. Dose-response relationships between physiological rates and hydrocarbon body burden were apparent.Key words: petroleum effects, Arctic, invertebrates, metabolism, enzymes, behaviour, biodegradation, hydrocarbon uptake, Baffin Island oil spill, dispersant Mots clés: effets dus au pétrole, Arctique, invertébréms, métabolisme, enzymes, comportement, biodécomposition, absorption d’hydrocarbures, projet de déversement de pétrole à l’île Baffin, agent de dispersion